Integração morfológica e modularidade craniana em roedores Equimídeos (Echimyidae: Rodentia) - Daniel, Carolline Raidan (2017)
The Echimyidae rodents are the most diverse family among the Caviomorphs rodents and are widespread in all Brazilian biomes. One of the most remarkable characteristics of this group is the wide ecomorphological diversity observed between clade members. For example, in this group there are semi-fossorial, scansorial, terrestrial, arboreal and semi-aquatic species. This high biological diversity arises questions regarding which factors influenced the high morphological disparity of these organisms. The aim of this study was to investigate such questions, grounded on morphological integration theory. Morphological integration theory refers to the interdependence of morphological traits observed in an organism. By assessing the relationship and magnitude of integration among cranial traits, it is possible to compare the patterns of modularity observed among groups of species, as well as to evaluate the evolutionary potential of a population, i.e. the capacity of a population to respond in the direction of natural selection. Some groups may exhibit the same patterns of association but differ in magnitude of integration, leading to a completely different evolutionary response between different taxa. In this study, the patterns of integration and modularity were evaluated in 7 Echimyidae species with different ecomorphological strategies: Euryzygomatomys spinosus, kannabateomys amblyonyx, Phyllomys blainvilii, Phyllomys pattoni, Proechimys roberti, Thrichomys apereoides and Trinomys paratus. The relationships between traits were evaluated comparing populations estimated covariance and correlations matrices. The presence of modules was investigated comparing the patterns of integration between traits and by using hypothetical matrices based on shared development/function. The results point to a common covariance and correlation pattern between equimids, supporting a constancy of these associations throughout the evolution of this group. On the other hand, a wide variation in the magnitude of integration was observed, and might have acted as an important factor on the emergence of the high diversity observed in this group. In addition, it was possible to detect the presence of the nasal and zygomatic modules in all groups, according to a priori established hypotheses. The oral module was detected only for the species K. amblyonyx, T. apereoides and T. paratus. Unlike the other species, only in T. apereoides we could not detect a cranial vault module. The skull base complex was not identified in any species. The observed patterns and magnitude of integration presented a strong influence on how equimids respond to natural selection. In this way, the evolutionary potential was variable between groups, with the most specialized diet species, K. amblyonyx, presenting a greater flexibility to respond in the direction of selection. In contrast, Phyllomys spp. presented the lowest rate of evolutionary flexibility. These results indicate that Echimyidae evolution was marked by the occupation of alternative evolutionary peaks according to the evolutionary potential of each species. Therefore, the data obtained in this study provided important evolutionary implications, allowing us to fill the existing gap between the high diversity and lifestyles present in this family.